The Role of Animated Videos in the Effectiveness of E-Learning at the High School Level - Lola Aulia Rizqi; Putri Slamet; Fivin Elyani; Yusrina Nafilah; Didik Himmawan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The quality of Indonesian education is currently still relatively low, one factor being that students experience various learning difficulties. Learning difficulties refer to situations in which students encounter specific obstacles in participating in the learning process and achieving optimal learning outcomes. This study employed a qualitative library research method. The digital era is a period of technological advancement, where information can be accessed quickly and easily through digital devices. Learning media are elements utilized by teachers to communicate knowledge to their students with the aim of capturing their attention and increasing their interest in specific subject matter. Animated videos are highly effective in conveying material. In the era of e-learning at the high school level, animated videos play a crucial role in increasing learning effectiveness. By presenting material in animated form, students and teachers can experience various benefits. Animated videos create engaging learning and increase student enthusiasm for learning. The use of animated videos as a learning medium in high schools has positive impacts. These advantages include increased effectiveness in information delivery, the ability to review topics, and the visualization of difficult concepts.